Chinese Herbal Formula Huayu-Qiangshen-Tongbi Decoction Compared With Leflunomide in Combination With Methotrexate in Patients With Active Rheumatoid Arthritis: An Open-Label, Randomized, Controlled, Pilot Study - Wu, Jiaqi; Chen, Xianghong; Lv, Yuan; Gao, Kaixin; Liu, Zehao; Zhao, Yue; Chen, Xiumin; He, Xiaohong; Chu, Yongliang; Wu, Xiaodong; Ou, Aihua; Wen, Zehuai; et al. (Frontiers in Medicine, 2020)
Background: The combination therapies of herbal products with disease-modifying anti-rheumatic drugs (DMARDs) are gradually adopted in the management of RA in China. Our study aims to evaluate the efficacy and safety of the combination therapy of Huayu-Qiangshen-Tongbi decoction (HQT), a patent Chinese medicine formula, and methotrexate (MTX) in treating active RA. Methods: This pilot study was a monocenter, open label, randomized controlled trial (RCT) with two parallel arms. Ninety active RA patients were randomly allocated to receive either HQT at a dose of 250ml twice daily or Leflunomide (LEF) at a dose of 20 mg once daily, and all participants received MTX at a dose of 10-15 mg once weekly. The primary efficacy end point was the proportion of patients who achieved 20% improvement in the American College of Rheumatology criteria (ACR20) after 24-week treatment. Results: 84.4% (76/90 ) patients completed the 24-week observation. In the intention-to-treat (ITT) analysis, the portion of patients achieving the ACR20 response criteria was 72.1% (31/43) in MTX + HQT group and 74.4% (32/43) in MTX + LEF group (p=0.808). No significant difference was observed in other parameters including ACR50, ACR70, clinical disease activity index good responses (cDAIs), European League against rheumatism (EULAR) good response, remission rate as well as low disease activity rate. The results of per-protocol (PP) analysis showed consistency with those of the ITT analysis. The mean change from baseline at week 24 for the van der Heijde modified total sharp score (mTSS) had no significant difference between two groups (3.59 ± 4.75 and 1.34 ± 8.67 in the MTX + HQT group and MTX + LEF group respectively, p=0.613). The frequency of adverse events was similar in both groups (12 case in the MTX + HQT and 16 cases in the MTX + LEF, p>0.05). Conclusions: In patients with active RA, treatment with the combination of HQT and MTX was associated with improvement in signs, symptoms and physical function. With a beneficial clinical response and acceptable tolerability, HQT or other Chinese medicine formula may be a good therapeutic option in the combination with MTX for RA treatment. Trial registration: ChiCTR-INR-16009031, http://www.chictr.org.cn/enindex.aspx